Influence of trampoline jumping on vertical jump performance - Nezu, T.; Muramatsu, S. (2001)
It becomes difficult and awkward to walk or jump after hopping on a trampoline. Disturbance of the perception system seems to be related to the symptom, however this has not been examined. Therefore, the purpose of this study was to elucidate the causes of the phenomenon. To confirm the existence of the symptoms, vertical jump (VJ) performance on a floor was compared between before and after trampoline jumps (TJ), and subjective feeling during the jumps was investigated by questionnaire. In the following study, EMG of the lower limb muscles was recorded during VJ on a floor, and VJ were filmed by a high-speed video-camera system before and after TJ for motion analysis. The maximal height of VJ decreased approximately 4 cm after TJ compared to the pre trampoline values. All subjects (n=10) answered that their body became heavier and that they felt their jumping performance decreased after TJ. Interestingly, seven out of 10 answered that the floor was harder after TJ compared to the pre-trampoline jump condition. EMG showed different activation patterns such that the gastrocnemius and vastus lateralis muscles were synchronized in VJ after TJ, but this is not the case before TJ. The motion analysis showed that the flexion of the hip and knee joints decreased in landing after TJ. These results suggest that TJ influenced the motion of VJ rapidly and it made the motion on the floor difficult to perform.